Transfer of sustainability training in land and conservation agriculture project: A behavioral study in Iran - Ataei, Pouria; Sadighi, Hassan; Abbasi, Enayat; Chizari, Mohammad (Frontiers in Sustainable Food Systems, 2022)
Introduction The transfer of sustainability training means applying the skills, attitudes, and knowledge acquired from training to the workplace to help sustainability and environmental protection. This study aimed to conduct a behavioral analysis of sustainability training transfer among farmers that had attended extension-training courses on the Land and Conservation Agriculture Project (LCAP) in Iran. Methods This research is quantitative and applied research that was carried out via a standardized survey. The research population was composed of all farmers who attended LCAP extension training courses in the three provinces of Golestan, Fars, and Khouzestanin, Iran (N=1204). 291 farmers were selected through stratified random sampling. A panel of experts established the content and face validity of the questionnaire. A pilot study was conducted to check the reliability by calculating Cronbach's alpha. Results and discussion Findings indicated that most farmers had sustainability training transfer at a high level. The analysis with a structural equation model revealed that perceived content validity, transfer design, opportunity to use, supervisor support, trainer characteristics, peer support, motivation to transfer, transfer effort -performance expectations, performance coaching, and personal capacity for transfer influenced farmers' intention to transfer sustainability training significantly and positively. Furthermore, farmers' intentions had a significant effect on their transfer of sustainability training. It can be concluded that a sustainability training transfer system is applicable to a training context related to sustainable agriculture and can provide a useful instrument for agricultural education organizations when investing in farmers' training.